2012
DOI: 10.1186/1471-2229-12-26
|View full text |Cite
|
Sign up to set email alerts
|

Fostered and left behind alleles in peanut: interspecific QTL mapping reveals footprints of domestication and useful natural variation for breeding

Abstract: BackgroundPolyploidy can result in genetic bottlenecks, especially for species of monophyletic origin. Cultivated peanut is an allotetraploid harbouring limited genetic diversity, likely resulting from the combined effects of its single origin and domestication. Peanut wild relatives represent an important source of novel alleles that could be used to broaden the genetic basis of the cultigen. Using an advanced backcross population developed with a synthetic amphidiploid as donor of wild alleles, under two wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
110
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(127 citation statements)
references
References 90 publications
14
110
1
2
Order By: Relevance
“…Therefore, these four QTLs were repeatedly detected in different populations. With respect to the QTLs for plant-type-related traits, no similar segment was found between our study and previously studies [26,27,55,56]. …”
Section: Discussionsupporting
confidence: 68%
“…Therefore, these four QTLs were repeatedly detected in different populations. With respect to the QTLs for plant-type-related traits, no similar segment was found between our study and previously studies [26,27,55,56]. …”
Section: Discussionsupporting
confidence: 68%
“…In the 2011/12 progenies evaluation, the estimated broad-sense heritability, the coefficients of genotypic determination and CVg/CVe ratio for pod yield and W100S were high (Table 1). These values are similar to those obtained with the BC 3 F 2 interspecific population reported by Fonceka et al (2012), and superior to those observed for advanced cultivated lines (Gomes and Lopes 2005), indicating a favorable condition for selecting superior genotypes for these traits under the current experimental conditions. Segregating plants for yield, pod uniformity and pod shape were selected in the interspecific progenies evaluated in the 2011/12 crop season, resulting in the introduction of new 43 runner type lines in the peanut breeding program of Embrapa.…”
Section: Resultssupporting
confidence: 87%
“…In the present study, high yielding interspecific progenies of runner market type with seed size for different markets were identified in the first backcross generation, attesting the potential for economic exploitation of the wild species reported by Stalker et al (1979) and Fonceka et al (2012). Partial resistant, high yield runner lines were selected and crossed with high yield/partial resistant cultivars to generate new breeding populations.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…For example, Selvaraj et al [4] identified two SSR markers, PM375 and Seq8D09, linked with pod length using bulked segregant analysis. Similarly, Shirasawa et al [18] identified three QTLs for pod length and two for pod width in an F 2 population while Fonceka et al [19] mapped three QTLs for pod length, six for pod width and two for hundred-pod weight in an advanced backcross population. More recently, Huang et al [15] detected one QTL for pod length, two QTLs for pod width and three QTLs for hundred-pod weight in an F 2:3 population.…”
Section: Introductionmentioning
confidence: 99%